2009
DOI: 10.4067/s0718-58392009000400004
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Rootstocks on Nitrogen, Phosphorus and Potassium Content in Petioles of Four Table Grape Varieties

Abstract: Four field trials were conducted at Vicuña Experimental Center (30°02' S, 70°44' W) located in the Coquimbo Region, Chile, over four seasons

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
25
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 11 publications
6
25
0
1
Order By: Relevance
“…Also, the Flame seedless cultivars grafted on control gave the lowest values in both seasons. Tangolar et al (1998) and Ibacache and Sierra (2009) on grafted grapes found the same results. Superior seedless and Thompson seedless cultivars grafted on Freedom, Polcin1103 and salt Greek rootstocks gave better potassium content,…”
Section: Effect Of Some Table Grape Scions Grafted On Different Rootssupporting
confidence: 75%
“…Also, the Flame seedless cultivars grafted on control gave the lowest values in both seasons. Tangolar et al (1998) and Ibacache and Sierra (2009) on grafted grapes found the same results. Superior seedless and Thompson seedless cultivars grafted on Freedom, Polcin1103 and salt Greek rootstocks gave better potassium content,…”
Section: Effect Of Some Table Grape Scions Grafted On Different Rootssupporting
confidence: 75%
“…Nikolaou et al (2000) reported an influence of rootstocks on the vigor of Thompson Seedless grapevines and it was directly influenced by the levels of cytokinin content that are associated with a high level of total N in the plant. Low phosphorus content was found with the rootstock Freedom in the cultivar Flame Seedless and Thompson Seedless and the rootstock Harmony in the cultivar Superior (Ibacache and Sierra, 2009). Grant and Matthews (1996) showed that with a sufficient application of phosphorus in the soil, the vines grafted on 110-R rootstock had higher content of the elements than other rootstocks.…”
Section: Primary Nutrients Statusmentioning
confidence: 94%
“…Therefore, in plants that are routinely grafted, such as grapevine (Vitis vinifera L.), rootstock effect on scion performance must be considered in the study of adaptability to stress conditions. Rootstocks provide tolerance to exogenous limiting factors, biotic (e.g., soilborne pests) and abiotic (e.g., salinity, water or oxygen deficit), while influencing the ecophysiological behaviour of the scion and its berry quality (Bavaresco and Lovisolo, 2000;Padgett-Johnson et al, 2000;Soar et al, 2006;Tramontini et al, 2012;de Souza et al, 2009;Ibacache and Sierra, 2009;Rizk-Alla et al, 2011;Marguerit et al, 2012). Stomata are considered direct responsible of optimizing the balance between carbon gain and water loss of the plant (Rogiers et al, 2012), and the patterns of their response, in terms of timing and intensity, are genetically determined (Chaves et al, 2010).…”
Section: Introductionmentioning
confidence: 99%